Communication and management at work - Klikauer, Thomas (Basingstoke, 2007)
"In today's workplaces, communication is becoming ever more important. At work, managerial regimes have a strong influence on the way we communicate. As our working environment is continuously moving towards post-industrialism, forms of workplace communication are changing with it. To discuss these changes comprehensively, historical-hermeneutical and critical-emancipatory theories are brought to bear to avoid yet another handy recipe book for effective managerial communication. The book positions work and management inside the historic development from early workshops and mass-manufacturing to today's managerial capitalism. With advancing managerialism, contemporary forms of workplace communication carry connotations of systematically distorted communication. The thesis of manipulated management talk has been linked to an Orwellian and Kafkaesque nightmare. Its anti-thesis, however, opens up possibilities for modern forms of communicative action and ideal speech."